Towards a Sustainable Campus: Designing a Socio-Technical Framework for IoT Energy Management Systems Supporting SDGs - Lutfi Afriansyah, Faisal; Dwi Puspitasari, Trismayanti; Arifin, Syamsul; Putro Sarwo Setyohadi, Dwi; Agus Kurniasari, Arvita (International Journal of Studies in Social Sciences and Humanities, 2026)
The increasing energy consumption in educational institutions presents a significant challenge for sustainable development. Smart campus initiatives, leveraging Internet of Things (IoT) technology, offer a promising solution for optimizing energy use, particularly for lighting and air conditioning (AC) systems. This study focuses on the design and development phase of a comprehensive social-technical framework for an IoT-based energy management system. The framework integrates ESP32 microcontrollers, Zigbee communication protocol, and a Digital Twin model to create an efficient and responsive control system. The primary objective is to establish a foundational design that addresses both the technical architecture and the crucial social aspects of user acceptance and integration within the campus environment, thereby supporting the achievement of Sustainable Development Goals (SDGs), specifically SDG 7 (Affordable and Clean Energy) and SDG 11 (Sustainable Cities and Communities). The methodology encompasses a user-centered design approach, involving stakeholder analysis and the development of a system prototype. Initial results include the successful design of the system architecture, the creation of a 3D Digital Twin model for visualization, and the development of a functional backend using Home Assistant. The study concludes that a robust social-technical framework is essential for the successful implementation of smart campus energy solutions and provides a roadmap for future deployment and evaluation, highlighting the importance of aligning technological innovation with user needs and institutional sustainability policies.